The Effectiveness of Combined Hatha Yoga and Tandem Walking Exercise on Sleep Quality: A Preliminary Study - Nikmatur Rosidah; Annisa Salsabila Budi Ningrum; Bayu Prastowo; Nungki Marlian Yuliadarwati; Ananda Viona Ameylia; Anup Acharya; Fahmi Rizal; Dwi Agung Prasetyo (The Indonesian Institute of Science and Technology Research, 2026)
To improve sleep quality, the use of a combination of relaxation techniques and physical fitness training has been suggested. This study aimed to assess the impact of a combined Hatha Yoga and Tandem Walking program on improving the quality of sleep in older adults in Malang, Indonesia. A one-group pre-post experimental design was used in this study. A total of 30 elderly participants participated and received a combination of Hatha yoga and tandem walking exercise for 30–45 minutes, for a total of 12 sessions. Pittsburgh sleep quality index used to measure the quality of sleep of the participants. Wilcoxon signed-rank test used for data analysis, and statistically significant set at 0.05. This study resulted in a substantial enhancement in sleep quality after 6 weeks of combined Hatha Yoga and Tandem Walking exercise, with the mean PSQI score decreasing from 9.32 ± 1.70 to 4.24 ± 0.75 and 81% of the participants experiencing good sleep quality (p = 0.001) after the intervention. The combination of Hatha Yoga and Tandem Walking is an effective and safe non-pharmacological intervention to improve sleep quality in older adults and support healthy aging. For optimal results, this intervention can be practiced regularly and incorporated into a program for senior communities.